Sosialisasi Pemilahan Sampah “Bersih Itu Keren” Di SD 2 Jegu, Tabanan, Bali - Nur Aprilya, Fira; Dwi Sanjani Mertaningsih, Ni Kadek; Lin, Fanny; Wardhiana, Nyoman Dana; Oktavia Gama, Adie Wahyudi; Lestara Permana, Gusi Putu (LPPM Univ. Ibn Khaldun Bogor, 2022)
Garbage has become a problem that is often found in today's environment. Especially in Jegu Village, Penebel District, Tabanan Regency, Bali Province, there is a waste problem that is quite worrying if it is not immediately handled with the right solution. In addition to having a negative impact on the environment and health, waste will also have a negative impact on the economy in Jegu Village. Starting from small things, namely providing an understanding to elementary school children about the importance of the role of children in maintaining cleanliness. The author approaches and educates by conducting socialization at Jegu 2 Elementary School with the theme